2010
DOI: 10.1111/j.1095-8649.2009.02532.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal resource selection by blue suckers Cycleptus elongatus

Abstract: Telemetry data were used to quantify seasonal resource selection and rank-preferred habitat types for blue suckers Cycleptus elongatus in the middle Missouri River and its tributaries, Iowa, Nebraska, South Dakota, U.S.A. Habitat diversity required by C. elongatus to complete its annual lifehistory cycle was evident by interseasonal variation in habitat selection. Tributaries and unchannelized portions of the middle Missouri River system were selected during the inferred spawning season (spring), habitats alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…BEND, SCC; Galat et al , ). Our results agree with Neely et al () who found that blue suckers did not use tributaries; however, our model further identified that secondary flowing channels were important to blue suckers whereas non‐flowing channels were not.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…BEND, SCC; Galat et al , ). Our results agree with Neely et al () who found that blue suckers did not use tributaries; however, our model further identified that secondary flowing channels were important to blue suckers whereas non‐flowing channels were not.…”
Section: Discussionsupporting
confidence: 92%
“…BEND, SCC; Galat et al, 2001). Our results agree with Neely et al (2010) who found that blue suckers did not use tributaries; however, our model further identified that secondary flowing channels were important to blue suckers whereas non-flowing channels were not. Smallmouth buffalo are found throughout Missouri and Mississippi rivers, primarily, in pools with slower, clearer water (Pflieger, 1997).…”
Section: Suckerssupporting
confidence: 92%
“…Information on trout habitat use could assist future management, conservation, and restoration efforts in several ways (Neely et al 2010). For example, it may aid in the identification of specific habitats that are necessary for completing certain life history requirements (Saiget et al 2007).…”
mentioning
confidence: 99%
“…When the GPSderived accuracy estimates were compared with the measured accuracy, an additional mean error of~1.7 m was apparent, but this source of variation was not statistically significant. Because GPS-derived accuracy was not different than measured accuracy, the use of GPS provides a simpler alternative to quantify accuracy and probably would not affect accuracy of geographic coordinate locations often collected in telemetry studies (Jordan et al 2006;Neely et al 2010;Trested et al 2011). Use of high precision GPS units, location augmentation techniques (e.g.…”
Section: Fisheries Management and Ecologymentioning
confidence: 99%